Impact of Lavender Aromatherapy on Decreased Anxiety in CKD Patients Undergoing Hemodialysis at Royal Prima Medan General Hospital in 2024 - Dinda Dilla Salsabila; Nova Rohimah Tanjung; Agnes Yolanda S; Julia Fransisca Sinaga; Putri Enzeliza Simanungkalit; Tiarnida Nababan (Jurnal Ners, 2025)
Patients often complain of anxiety caused by feelings of loss because hemodialysis interferes with their normal life. This study was conducted to see the impact of lavender aromatherapy on decreased anxiety in patients with CKD undergoing hemodialysis at Royal Prima Medan General Hospital in 2024. Quantitative with a quasi-experimental design is methods of this study through a one group pre-test post-test design. The population to be studied was all chronic kidney disease patients undergoing hemodialysis in November 2024 as many as 127 people at Royal Prima Medan General Hospital in 2024 and the sample studied was 56 respondents. The information collection strategy in this inquire about was to utilize essential information and auxiliary information. The information that has been prepared and displayed at that point analyzed univariately and displayed within the frame of recurrence tables and bivariate investigation utilizing the pairing T test. The results of the research conducted on 56 respondents showed a Sig. (2-tailed) 0.000. This study concluded that there was a significant influence between pre and post giving lavender inhalation aromatherapy on decreased anxiety in clients with chronic kidney failure undergoing hemodialysis at Royal Prima Medan General Hospital in 2024.